2013
DOI: 10.1021/bi301635f
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Folding of Human Peripheral Myelin Protein 22, a Tetraspan Membrane Protein

Abstract: Misfolding of the α-helical membrane protein peripheral myelin protein 22 (PMP22) has been implicated in the pathogenesis of the common neurodegenerative disease known as Charcot-Marie-Tooth disease (CMTD) and also several other related peripheral neuropathies. Emerging evidence suggests that the propensity of PMP22 to misfold in the cell may be due to an intrinsic lack of conformational stability. Therefore, quantitative studies of the conformational equilibrium of PMP22 are needed to gain insight into the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 79 publications
3
75
0
Order By: Relevance
“…Where known, measured stabilities of helical bundle and β barrel membrane proteins are comparable to values observed for globular proteins (1.5-10 kcal/mol [15,49], corresponding to a folding equilibrium constant of ∼ 10-10 8 ). Although in a two-state folding transition, the folded and unfolded states are considered to be of fixed energies, a more realistic interpretation is to consider these as ensembles.…”
Section: B Equilibrium Properties Of the Ensemble Of Statessupporting
confidence: 58%
“…Where known, measured stabilities of helical bundle and β barrel membrane proteins are comparable to values observed for globular proteins (1.5-10 kcal/mol [15,49], corresponding to a folding equilibrium constant of ∼ 10-10 8 ). Although in a two-state folding transition, the folded and unfolded states are considered to be of fixed energies, a more realistic interpretation is to consider these as ensembles.…”
Section: B Equilibrium Properties Of the Ensemble Of Statessupporting
confidence: 58%
“…Interestingly, conformational stability measurements of diacylglycerol kinase (DAGK) (Lau & Bowie, 1997), bacteriorhodopsin (bR) (Curnow & Booth, 2007), the KcsA potassium channel (Barrera et al, 2008), and aquaglyceroporin GlpF (Veerappan et al, 2011) have suggested large thermodynamic separation of the native and denatured reference states (Δ G unf = 16 to 31 kcal/mol). On the other hand, studies of disulfide bond reducing protein B (DsbB) (Otzen, 2003), galactose transporter GalP (Findlay et al, 2010), lactose permease LacY (Harris et al, 2014), human peripheral myelin protein 22 (PMP22) (Schlebach et al, 2013), and the rhomboid protease (Baker & Urban, 2012) have suggested a more modest thermodynamic preference for their native conformations (Δ G unf = 0 to 4.5 kcal/mol). Can it be that the range of thermodynamic stabilities of single domain wild-type α-helical membrane proteins varies by more than an order of magnitude?…”
Section: Energetics Of Folding and Misfolding Of α-Helical Membranmentioning
confidence: 99%
“…Similar to soluble proteins (Brockwell & Radford, 2007), kinetic intermediates of helical membrane proteins can form within milliseconds of the initiation of folding from detergent-denatured states (Allen et al, 2004b; Booth et al, 1995; Krishnamani & Lanyi, 2011; Lu & Booth, 2000; Otzen, 2003). However, complete refolding and/or oligomerization from can require anywhere from minutes to days in vitro (Allen et al, 2004b; Cao et al, 2011; Jefferson et al, 2013; Krishnamani & Lanyi, 2011; Riley et al, 1997; Schlebach et al, 2012; Schlebach et al, 2013). The folding of the soluble denatured forms of β-barrel membrane proteins into membranes also appears to be quite slow (Burgess et al, 2008; Gessmann et al, 2014; Huysmans et al, 2010; Huysmans et al, 2012), though in this case the rate-limiting step seems to involve the transfer of the unfolded protein from the aqueous phase to the membrane phase (Gessmann et al, 2014; Huysmans et al, 2010; Huysmans et al, 2012).…”
Section: Energetics Of Folding and Misfolding Of α-Helical Membranmentioning
confidence: 99%
See 2 more Smart Citations